Lysosomal acid lipase and lipophagy are constitutive negative regulators of glucose-stimulated insulin secretion from pancreatic beta cells. - Pearson, G; Mellett, N; Chu, K; Cantley, J; Davenport, A; Bourbon, P; Cosner, C; Helquist, P; Meikle, P; Biden, T (2014)
AIMS/HYPOTHESIS: Lipolytic breakdown of endogenous lipid pools in pancreatic beta cells contributes to glucose-stimulated insulin secretion (GSIS) and is thought to be mediated by acute activation of neutral lipases in the amplification pathway. Recently it has been shown in other cell types that endogenous lipid can be metabolised by autophagy, and this lipophagy is catalysed by lysosomal acid lipase (LAL). This study aimed to elucidate a role for LAL and lipophagy in pancreatic beta cells. METHODS: We employed pharmacological and/or genetic inhibition of autophagy and LAL in MIN6 cells and primary islets. Insulin secretion following inhibition was measured using RIA. Lipid accumulation was assessed by MS and confocal microscopy (to visualise lipid droplets) and autophagic flux was analysed by western blot. RESULTS: Insulin secretion was increased following chronic (≥ 8 h) inhibition of LAL. This was more pronounced with glucose than with non-nutrient stimuli and was accompanied by augmentation of neutral lipid species. Similarly, following inhibition of autophagy in MIN6 cells, the number of lipid droplets was increased and GSIS was potentiated. Inhibition of LAL or autophagy in primary islets also increased insulin secretion. This augmentation of GSIS following LAL or autophagy inhibition was dependent on the acute activation of neutral lipases. CONCLUSIONS/INTERPRETATION: Our data suggest that lysosomal lipid degradation, using LAL and potentially lipophagy, contributes to neutral lipid turnover in beta cells. It also serves as a constitutive negative regulator of GSIS by depletion of substrate for the non-lysosomal neutral lipases that are activated acutely by glucose.